A study of factors influencing teachers’ psychological well-being using the focus group method - KAZAKOVA, Olga (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. In the context of increasing professional demands and social instability, the issue of teachers' psychological well-being is gaining particular relevance. The rising levels of emotional burnout among educators both in Ukraine and globally highlight the need to explore not only individual, but also organizational and socio-environmental determinants of well-being. The study aimed to identify key subjective factors influencing psychological well-being among teachers using the focus group method.Methods. A qualitative focus group interview approach was employed. In January 2025, seven online focus groups (N = 62) were conducted with teachers from various Ukrainian regions. Discussions followed a standardized scenario, were transcribed, and subjected to qualitative content analysis. Thematic clustering was applied based on semantic proximity.Results. Five major clusters of factors contributing to teacher well-being were identified: (1) social-organizational (financial stability, administrative support, reduced bureaucracy); (2) interpersonal (peer support, communication with students and parents); (3) personal-resource (self-regulation, restorative rituals, somatic practices); (4) macro-social (war, economic instability, information overload); (5) existential-professional (sense of meaning, positive feedback from students). Unique factors included the need for aesthetics, creativity, and pedagogical autonomy.Conclusions. Teachers’ psychological well-being is shaped by an interplay of personal resources and structural conditions. Imbalanced demands and lack of systemic support increase reliance on compensatory coping mechanisms. The findings emphasize the importance of safe educational environments, reduced administrative pressure, and opportunities for professional self-fulfillment during times of crisis. The study highlights the value of focus groups for in-depth exploration of complex psychological phenomena in professional communities.
Keywords: psychological well-being; teachers; emotional burnout; focus group; professional self-fulfillment; self-regulation; social factors; educational environment